Outcomes of severely ill patients with AIDS treated with efavirenz or dolutegravir: a multicenter, observational study - Brites, Carlos; Lacerda, Marcus; Sprinz, Eduardo; Bay, Monica; Pinto, Gustavo; Azevedo, Pollyanna; Luz, Estela; Lins-Kusterer, Liliane; Netto, Eduardo M. (Frontiers in Medicine, 2024)
Background – Currently, integrase inhibitors (INI) compose the preferred initial therapy for AIDS patients. There is scarce information on DTG use in late-presenters people living with HIV (PLHIV). Objectives – To compare the effect of DTG or EFV-based regimens on outcomes of patients with advanced AIDS. Methods - We compared two cohort of consecutive symptomatic AIDS patients (WHO stage 4, CD4 count<50 cells/ml) starting therapy with DTG (2018 to 2021, prospective cohort) or EFV-based regimens (2013 to 2016, retrospective cohort) from 5 Brazilian cities. Main endpoints were early (all cause) mortality, viral suppression at 24 and 48 weeks, changes in CD4 count and changes in initial therapy (any reason). Results - We included all eligible patients in a consecutive way (both groups) until reaching 92 individuals per arm. Median baseline CD4 count (20 vs 21 cells/ml), and median HIV plasma viral load (5.5 copies/ml log10) were identical across groups. Viral suppression rates were higher in DTG than in EFV group at 24 (67.4% vs 42.4%,) and at 48 weeks (65.2% vs 45.7%, p<0.001 for both comparisons). More patients in DTG than in EFV group presented with CD4 >200 cells/ml, at 48 weeks (45% vs. 29%, p=0.03). Treatment changes (ITT, M=F) were significantly more frequent in EFV group (1% vs. 17%, p<0.0001). Relative mortality rate was 25% lower in DTG groups, but without statistical significance. Conclusions – We detected a higher rate of virological suppression and greater treatment durability were observed in patients with advanced AIDS with DTG than in those treated with EFV